The organic farming in Poland compared to selected countries of the European Union versus sustainable development - Hanna Adamska; Stanisław Minta (Economic and Environmental Studies (E&ES), 2019)
Organic farming is based on care for the proper functioning of ecosystems, organisms with the simultaneous production of wholesome food raw materials. It fits into the concept of sustainable development by implementing the aspects: economic, social and environmental. Theoretical and empirical considerations concern the years 2006-2016 and are based on specialist literature and Eurostat data. The aim of the study was to determine the state of organic farming in Poland against the background of selected EU countries (Denmark, Germany, Spain, France, Italy, Sweden, Portugal, Greece). Based on the investigation, we can see that organic farming has been developing dynamically in recent years on the global, European and Polish scales. There is a visible increase in the number of organic farms and the increase in the area of agricultural organic lands in the European Union. In the case of Poland, the importance of organic farming is growing and this process is often stronger than in other compared countries. On the basis of the conducted research it was shown that there are significant differences in the structure of organic agricultural land between chosen EU countries. In northern countries (Denmark, Sweden, Poland), arable land is predominant, while in the southern EU (Spain, Italy, Greece, Portugal), the share of permanent crops was much higher than in the other analysed countries.
Keywords: O13; Q01; Q15; 330; organic farming; economic development; sustainable development; the European Union